ENVIRONMENTAL EDUCATION ALLIED TO RECOVERY METHOD FOR SPRING PLANTING IN A LOCATED IN URBAN AREA OF THE CITY OF ITAPIRA - SP - Martelli, Anderson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Currently, concern for the environment is present in the lives of most of the population. Studies on the state of conservation of water sources and the structure of its riparian show is extremely important to support programs of restoration of these ecosystems. This article discusses the importance of restoring vegetation by tillage in a permanent preservation area located around two springs found in the urban perimeter of Itapira – SP through environmental education programs developed by the Department of Agriculture and Environment with the members of the Intermunicipal Consortium of Sanitation Water Circuit and surrounding residents. These vegetation belts exert barrier function and protection of watercourses, serving as ecological corridors, linking forest fragments, allowing the transit of animals and removing them from isolation and fixation of atmospheric carbon, thereby contributing to the reduction of greenhouse effect. The study seeks to further subsidize the authorities and society to raise awareness and preservation of the natural environment, since there is a lack of information and concern about the possible threat of water scarcity that is both trumpets around the world..